2016
DOI: 10.1007/s10103-016-2081-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low-level laser therapy and epidermal growth factor on the activities of gingival fibroblasts obtained from young or elderly individuals

Abstract: This study evaluated the effects of low-level laser therapy (LLLT) and epidermal growth factor (EGF) on fibroblasts obtained from young and elderly individuals. Gingival fibroblasts from young (Y) and elderly (E) individuals were seeded in wells of 24-well plates with Dulbecco's modified Eagle's medium (DMEM) containing 10 % of fetal bovine serum (FBS). After 24 h, the cells were irradiated (LASERTable-InGaAsP-780 ± 3 nm, 25 mW, 3 J/cm) or exposed to EGF (100 μM). After 72 h, cells were evaluated for viability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…Immediately after the cells were exposed to LPS, PBM was carried out by an InGaAsP laser diode prototype (LaserTABLE) that has been widely used for assessment of the effects of laser irradiation on different cultured cell types, such as epithelial cells, gingival fibroblasts, osteoblasts and odontoblasts . Three irradiations were performed with a 24 h interval between each irradiation using a dose of 3 J cm −2 with a power of 25 mW.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immediately after the cells were exposed to LPS, PBM was carried out by an InGaAsP laser diode prototype (LaserTABLE) that has been widely used for assessment of the effects of laser irradiation on different cultured cell types, such as epithelial cells, gingival fibroblasts, osteoblasts and odontoblasts . Three irradiations were performed with a 24 h interval between each irradiation using a dose of 3 J cm −2 with a power of 25 mW.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have shown that PBM causes significant biostimulatory effects in oral mucosal cells, characterized by increased cell proliferation and migration as well as synthesis of growth factors and collagen type I . Consequently, specific parameters of PT have been used largely to accelerate tissue repair as well as to modulate the local expression of inflammatory cytokines by gingival fibroblasts .…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory cells secrete essential cytokine and growth factors necessary for angiogenesis and stromal cell migration (Eming, Krieg, & Davidson, 2007). With regard to a recent report demonstrating a substantial increase in vascular endothelial growth factor (VEGF) synthesis by human gingival fibroblasts exposed to EGF in vitro (Pansani et al, 2017), the elevated neovascularization EFG1 and EGF10 is not a surprising finding and strongly suggests the ability of rhEGF to promote oral mucosa wound healing by facilitating angiogenesis in addition to an earlier resolution of inflammation (Gainza et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The available data suggest the promise of EGF purposed at improving oral wound healing. To recapitulate, stimulation of proliferation and migration of oral keratinocytes, stimulation of gingival fibroblasts mitogenesis and increase of collagen synthesis (Kim et al., ; Pansani et al., ; Ramineni, Fowler, Fisher, Cunningham, & Puleo, ) are among the cellular events through which exogenous EGF is harnessed to facilitate the wound repair in vitro. Nevertheless, whether EGF‐based treatment is able to facilitate the repair of acute injuries healing by secondary intention remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…While some studies found similar results of increased COL1 gene expression by irradiated fibroblasts (Martignago et al, 2015;Pansani et al, 2017), others concluded that the amount of COL1 expression was not different between irradiated and non-irradiated fibroblasts (Pereira et al, 2002;Marques et al, 2004). The rationale behind this distinct outcome is the different cell type (gingival fibroblasts rather than pulp fibroblasts), wavelength (904 nm), irradiance (3 J/cm 2 ), and application time.…”
Section: Resultsmentioning
confidence: 88%